1998
DOI: 10.1126/science.282.5397.2226
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Polar Auxin Transport by AtPIN1 in Arabidopsis Vascular Tissue

Abstract: Polar auxin transport controls multiple developmental processes in plants, including the formation of vascular tissue. Mutations affecting the PIN-FORMED (PIN1) gene diminish polar auxin transport in Arabidopsis thaliana inflorescence axes. The AtPIN1 gene was found to encode a 67-kilodalton protein with similarity to bacterial and eukaryotic carrier proteins, and the AtPIN1 protein was detected at the basal end of auxin transport–competen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
1,036
1
17

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 1,402 publications
(1,095 citation statements)
references
References 31 publications
41
1,036
1
17
Order By: Relevance
“…The Bjpin1 cDNA has a length of 2557 nucleotides with an open reading frame present between nucleotides 126 (ATG) and 2042 (TGA). The predicted protein contained 639 amino acid residues and had a molecular mass of 7 0 kDa, similar to that of previously reported AtPIN1 [21] and AtPIN2/EIR1 [22]. The calculated isoelectric point of BjPIN1 was 8.88.…”
Section: Cloning Of Bjpin1 From B Junceasupporting
confidence: 81%
See 3 more Smart Citations
“…The Bjpin1 cDNA has a length of 2557 nucleotides with an open reading frame present between nucleotides 126 (ATG) and 2042 (TGA). The predicted protein contained 639 amino acid residues and had a molecular mass of 7 0 kDa, similar to that of previously reported AtPIN1 [21] and AtPIN2/EIR1 [22]. The calculated isoelectric point of BjPIN1 was 8.88.…”
Section: Cloning Of Bjpin1 From B Junceasupporting
confidence: 81%
“…The Atpin1 gene, isolated through En-tagging method, was found to encode a protein with similarity to bacterial and eukaryotic carrier proteins. AtPIN1 protein was detected at the basal end of auxin transport-competent cells in vascular tissues [21]. These studies strongly suggested that AtPIN1 might act as a transmembrane component of the auxin efflux carrier and play a role in auxin transport from shoot apex to root tissue in stems.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Recently several pin genes have been cloned by Dr. Palme s group in Max-Planck Institute of Plant Breeding in Köln, and one of them (pin1) is correlated to the mutant pin1-1 described by Okada. Due to the PIN protein predicted from pin1 sequence having typical membrane domain, they consider that PIN1 may be an auxin transporter [22]. According to the fact that protein kinase inhibitors could reduce the auxin polar transport activity in etiolated pea seedlings, it was suggested that inhibition of protein phosphorylation could lead to the hindrance of the auxin-exporting function of NPA receptors [23].…”
Section: Discussionmentioning
confidence: 99%